Older or Wealthier? The Impact of Age Adjustments on the Wealth Inequality Ranking of Countries - Ingvild Almås; Magne Mogstad (Statistics Norway, Research Department, 2009)
Differences in individual wealth holdings are widely viewed as a driving force of economic inequality. However, as this finding relies on cross-section data, we may confuse older with wealthier. We propose a new method to adjust for age effects in cross-sections, which eliminates transitory wealth inequality due to age, yet preserves inequality arising from other factors. This new method is superior to existing methods, like the much used Paglin-Gini, which is shown to have several problems. A new cross-country comparable database reveals that the choice of method is empirically important: Existing methods yield erroneous wealth inequality rankings of countries.
Keywords: D31; D63; D91; E21; 330; Wealth inequality; Life cycle; Age adjustments; Gini coefficient.